A replacement name for Asthenes wyatti perijanus Phelps 1977 - Chesser, R. Terry (Zootaxa, 2016)
A recent near-complete phylogeny of the avian family Furnariidae (Derryberry et al. 2011) found a number of discrepancies between the phylogeny and the then-current taxonomy of the group, and several changes were proposed to reconcile the taxonomy of the family with the phylogeny. Among these was the merging of the genus Schizoeaca Cabanis 1873 into Asthenes Reichenbach 1853 (Derryberry et al. 2010). This change has now been generally adopted. The Committee on Classification and Nomenclature (South America) of the American Ornithologists’ Union (Remsen et al. 2015) passed a proposal to merge the genera in 2010, and recent global reference works (e.g., Dickinson & Christidis 2014) have likewise adopted the lumping of these genera.